Gender and organized crime in Italy: Women's agency in Italian mafias - Ingrascì, Ombretta (Dublin I. B. tauris; Bloomsbury, 2021)
In this comprehensive study of the role of women in the Italian mafia, Ombretta Ingrasci assesses the roles and spaces of women within traditionally male, patriarchal organized crime units. The study draws on an extensive range of research, legal reports and interviews with women involved with the mafia, public officials and police. Placed within a framework of political, social, cultural and religious history, post-1945, this book provides an excellent history of women and organized crime in modern Italy.
Keywords: Security and Foreign Affairs Sector; Organized crime; Women's Agency in Italy; Women in crime